Multidimensional Integrated Counseling to Overcome Self-Efficacy Deficits in Islamic Boarding School Based College Students.: Konseling Terintegrasi Multidimensional Mengatasi Defisit Efikasi Diri pada Mahasiswa Perguruan Tinggi Berbasis Pesantren. - Hidayat, Nur; ‘Ulya, Rifqi Minchatul; Al Waro, Miftahul Alam (Academia Open, 2026)
General Background Female students balancing university coursework with religious learning face overlapping scholastic, social, and familial pressures. Specific Background When welfare services treat these multidimensional struggles separately, they inadvertently diminish the academic confidence of the student. Knowledge Gap Existing literature predominantly examines these challenges as discrete variables, lacking a holistic understanding of how simultaneous boarding routines and parental expectations interact. Aims This study examined an eleven-session therapeutic intervention targeting the overlapping learning, relational, and familial struggles of a female undergraduate. Results Thematic analysis revealed that diminished academic confidence stemmed from memorization difficulties, dormitory rotation policies, and internalized maternal doubt. Following the intervention, the participant successfully restructured negative family narratives, initiated peer assistance requests, and formulated independent study plans. Novelty Unlike isolated, single-domain approaches, this qualitative single-case study provides a dynamically synthesized therapeutic framework combining person-centered, solution-focused, and cognitive-behavioral techniques. Implications These findings offer institutional welfare supervisors a culturally embedded, comprehensive model to foster student well-being and scholastic persistence. Highlights Cognitive and behavioral therapies successfully manage overlapping familial and scholastic pressures. Recurrent dormitory rotations paradoxically exacerbate peer isolation among introverted female students. Restructuring internalized maternal doubt restores active study planning and help-seeking behaviors. Keywords Integrated Multidimensional Counseling; Academic Self Efficacy; Islamic Residential Education; Social Adaptation; Single Case Study